2015
DOI: 10.1016/j.ijfoodmicro.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and localization of human norovirus and animal caliciviruses in fresh produce

Abstract: Fresh produce is a high risk food for human norovirus (NoV) contamination. To help control this pathogen in fresh produce, a better understanding of the interaction of human NoV and fresh produce needs to be established. In this study the attachment of human NoV and animal caliciviruses (murine norovirus, MNV-1; Tulane virus, TV) to fresh produce was evaluated, using both visualization and viral enumeration techniques. It was found that a human NoV GII.4 strain attached efficiently to the Romaine lettuce leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Washing of fresh produce may prove ineffective to remove microorganisms, as they may remain attached to plant surfaces (DiCaprio et al, 2015), or become internalized in the edible parts of the plant (Franz & van Bruggen, 2008), and thus, are not accessible for efficient removal. In addition, the water used to wash fresh produce can be a source of microbial contamination (CDC, 1989;Hedberg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Washing of fresh produce may prove ineffective to remove microorganisms, as they may remain attached to plant surfaces (DiCaprio et al, 2015), or become internalized in the edible parts of the plant (Franz & van Bruggen, 2008), and thus, are not accessible for efficient removal. In addition, the water used to wash fresh produce can be a source of microbial contamination (CDC, 1989;Hedberg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that HuNoV VLP, TV, and MNV preferentially aggregate inside lettuce stomata, suggesting that the three viruses exhibit similar patterns of attachment to lettuce leaves (53). However, specific binding was not investigated in that study.…”
Section: Discussionmentioning
confidence: 89%
“…After viruses attach to the surface of lettuce cell wall they bind by multiple carbohydrate moieties and electrostatic force may play a major role in controlling virus adsorption and enhance virus persistence on the leaf surface. Human norovirus-like particles associate with the surface of Romaine lettuce aggregating in and around the stomata, while in green onions between the cells of the epidermis and cell walls of both the shoots and roots, what suggests that viruses differ in their localization patterns to varieties of fresh produce [15]. Also, there is a need to understand the factors influencing the survival/persistence characteristics of human norovirus on pre-harvest leafy greens to develop proper measures to prevent contamination [16].…”
Section: Transmission and Associated Foodsmentioning
confidence: 99%